2002
DOI: 10.1074/jbc.m112365200
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis RecA Intein Possesses a Novel ATP-dependent Site-specific Double-stranded DNA Endonuclease Activity

Abstract: Mycobacterium tuberculosis recA harbors an intervening sequence in its open reading frame, presumed to encode an endonuclease (PI-MtuI) required for intein homing in inteinless recA allele. Although the proteinsplicing ability of PI-MtuI has been characterized, the identification of its putative endonuclease activity has remained elusive. To investigate whether PI-MtuI possesses endonuclease activity, recA intervening sequence was cloned, overexpressed, and purified to homogeneity. Here we show that PI-MtuI bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
(52 reference statements)
4
30
0
Order By: Relevance
“…The exact sequence of events that lead to recognition and cleavage of DNA by homing endonucleases is poorly understood. In addition, in no case the molecular mechanism underlying cleavage of ectopic DNA sites by an intein endonuclease has been elucidated.Mycobacterium tuberculosis RecA intein (PI-MtuI) 1 is a member of the LAGLIDADG superfamily of homing endonucleases (15)(16)(17)(18). In previous studies, we showed that PI-MtuI is a novel homing endonuclease, which inflicted a staggered doublestrand break 24 bp upstream of the intein insertion site in the inteinless recA allele (henceforth called cognate site) (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exact sequence of events that lead to recognition and cleavage of DNA by homing endonucleases is poorly understood. In addition, in no case the molecular mechanism underlying cleavage of ectopic DNA sites by an intein endonuclease has been elucidated.Mycobacterium tuberculosis RecA intein (PI-MtuI) 1 is a member of the LAGLIDADG superfamily of homing endonucleases (15)(16)(17)(18). In previous studies, we showed that PI-MtuI is a novel homing endonuclease, which inflicted a staggered doublestrand break 24 bp upstream of the intein insertion site in the inteinless recA allele (henceforth called cognate site) (18).…”
mentioning
confidence: 99%
“…In previous studies, we showed that PI-MtuI is a novel homing endonuclease, which inflicted a staggered doublestrand break 24 bp upstream of the intein insertion site in the inteinless recA allele (henceforth called cognate site) (18). Typically, Mg 2ϩ is the preferred metal ion and the only cofactor required for cleavage of inteinless alleles by the LAGLIDADG family of homing endonucleases.…”
mentioning
confidence: 99%
“…The K d values for PI-MleI and its variants are comparable to the K d values determined for the binding of other LAGLIDADG-type enzymes to their cognate DNA sequences. 12,36,37 The specificity of interaction of PI-MleI variants with target DNA sequence was determined using a salt-titration assay. The higher salt-titration midpoint value ($ 0.3 M), except in the case of D128A variant (Fig.…”
Section: Dna-binding Analysis Of Pi-mlei and Its Variants By Electropmentioning
confidence: 99%
“…[3][4][5] Several lines of evidence suggest that a variety of divalent cations can support cleavage reactions by HEases, but they do not influence DNA-binding. [10][11][12] Most HEases prefer oxophilic Mg 2þ , some use thiophilic Mn 2þ , whereas others can use both for optimal catalysis. 10,11 Cocrystal structures of several LAGLI-DADG endonucleases including I-CreI, 13 I-MsoI, 14 and I-SceI 15 indicated the presence of three divalent cations, coordinated by a pair of conserved aspartate residues at the active site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation